Health data protection: the challenge of legislative harmonization in Latin America - Muñoz-del-Carpio-Toia, Agueda (2023)
The protection of personal data in health systems requires special measures and procedures to ensure that the privacy of the information is not violated. Advances in digital technology and access to real-time transmission of personal, family, clinical, and laboratory data of patients and/or study subjects may compromise the protection of this information. The privacy of personal data in health in times of pandemic has meant a greater challenge, that is why this unique contribution is presented, whose objective is to identify the ethical and regulatory safeguards in terms of data protection to guarantee full respect for the privacy rights of people and the confidentiality of their data, under the context of health care, especially in conditions of health crisis, such as the one experienced during the SARS-CoV-2 pandemic. It also proposes a legislative harmonization in Latin America, on privacy and protection of personal data.